Pengaruh Kerja Tim, Kepuasan Kerja, Niat Untuk Berhenti Terhadap Kinerja Karyawan - Nurdiannova, Arief; Handu, Atanasius (Akuntansi dan Manajemen, 2024)
Every company needs quality employee performance to achieve company goals. This study aims to determine the effect of teamwork, job satisfaction, and intention to quit on employee performance. Teamwork is the implementation of work in groups in a company. Job satisfaction is a feeling of satisfaction with the work that has been done. Intention to quit is a feeling of wanting and trying to leave the current workplace according to the employee's wishes. Meanwhile, employee performance is the quality and quantity of employee work according to their responsibilities. The population used in this study were employees of PT. Multi Energy Nusantara as many as 75 respondents with census techniques, so that the sample obtained was also 75 respondents. Data were collected through a questionnaire survey and analyzed using multiple linear regression analysis. Based on the test results, it shows several conclusions that partially, teamwork does not affect employee performance, job satisfaction has a positive effect on employee performance, and employee intention to quit has an effect on employee performance at PT. Multi Energy Nusantara. Meanwhile, simultaneously teamwork, job satisfaction, and intention to quit have an effect on employee performance at PT. Multi Energy Nusantara.